Administrative decision-making amid competing public sector values: Confederate statue removal in Baltimore, Maryland. (3rd July 2019) - Elias, Nicole M.; McCandless, Sean; Chordiya, Rashmi
ABSTRACT: Confederate monuments conjure competing public sector values. Like many cities in the USA, Baltimore, Maryland had monuments honoring the "Lost Cause of the Confederacy". Such monuments, usually constructed during periods of racial strife, typically feature prominent figures of the Confederacy, such as generals. Proponents of such monuments argue these monuments honor historical figures that shaped US history. Opponents assert monuments symbolize racist ideals and reinforce inequality, particularly for African Americans. Baltimore had four monuments until 2017. In the aftermath of two racially charged incidents following decades of social injustices, the Mayor of Baltimore, Catherine Pugh, ordered the monuments' removal in August 2017. This case examines the details and rationale surrounding Pugh's decision in the context of competing public sector values. The knowledge and skills gained from this case study can be applied to a range of public administration and policy issues involving social justice, administrative competencies, and leadership.